2017
DOI: 10.1016/j.bbagen.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of human DJ-1 in distinct Cys106 oxidative states and their relevance to its loss of function in disease

Abstract: DJ-1 (PARK7) is a multifunctional protein linked to the onset and progression of a number of diseases, most of which are associated with high oxidative stress. The Cys106 of DJ-1 is unusually reactive and thus sensitive to oxidation, and due to high oxidative stress it was observed to be in various oxidized states in disease condition. The oxidation state of Cys106 of DJ-1 is believed to determine the specific functions of the protein in normal and disease conditions. Here we report molecular dynamics simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
31
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 60 publications
10
31
0
1
Order By: Relevance
“…Additionally, the cytoprotective interaction of DJ-1 with apoptosis signal-regulating kinase 1 (ASK1) was mediated by SO 2 H and modulated by peripheral C46 and C53 (29,30). However, high oxidation of C106 to SO 3 H results in aggregated and inactive DJ-1, and has been correlated with the increased progression of disease including PD where oxidative stress is a part of the pathophysiology (27,31).…”
Section: The Multifaceted Roles Of Dj-1 As An Antioxidantmentioning
confidence: 99%
“…Additionally, the cytoprotective interaction of DJ-1 with apoptosis signal-regulating kinase 1 (ASK1) was mediated by SO 2 H and modulated by peripheral C46 and C53 (29,30). However, high oxidation of C106 to SO 3 H results in aggregated and inactive DJ-1, and has been correlated with the increased progression of disease including PD where oxidative stress is a part of the pathophysiology (27,31).…”
Section: The Multifaceted Roles Of Dj-1 As An Antioxidantmentioning
confidence: 99%
“…Canet-Aviles et al observed that cysteine-sulfinic acid formation in DJ-1 is necessary for mitochondrial targeting and neuroprotection [ 307 ], and consistent with this, Zhou et al demonstrated that the sulfinic DJ-1 isoform prevents α -synuclein fibrillation [ 308 ]. Conversely, in the presence of high levels of oxidative stress, DJ-1 is oxidised to the sulfonic form; this isoform is inactive and predisposed to aggregate formation, and indeed, this overoxidised isoform has been detected in brains from Parkinson's patients [ 309 , 310 ]. In addition, Ozawa et al highlighted the crucial role of DJ-1 in the nitrosylation of Parkin, and suggested that DJ-1 inactivation reduces mitophagy, leading to mitochondrial dysfunction and Parkinson's pathogenesis [ 311 ].…”
Section: Autophagy and Redoxtasis Crosstalkmentioning
confidence: 99%
“…This irreversible form has been suggested to inactivate DJ-1 function 2224 ; however, the mechanism is not well understood. Accumulation of Cys106-SO 3 − DJ-1 has been correlated to diseases development where oxidative stress is a part of pathophysiology 25 . We have recently reported the cytoprotective role of DJ-1 against ATII cell injury in smokers 26 .…”
Section: Introductionmentioning
confidence: 99%